(untitled) (Journal of the College of Basic Education, 2023)
The outbreak of the Iran-Iraq war coincided with the arrival of Chinese leader Deng Xiaoping to power in China, and the transformation of China’s domestic and foreign policy from ideology to pragmatism. In light of this, China defined its policy towards Iran during the Iran-Iraq war stage